2018
DOI: 10.1104/pp.17.01714
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal RNA Biogenesis and Its Response to Chilling Stress in Oryza sativa

Abstract: Ribosome biogenesis is crucial for plant growth and environmental acclimation. Processing of ribosomal RNAs (rRNAs) is an essential step in ribosome biogenesis and begins with transcription of the rDNA. The resulting precursor-rRNA (pre-rRNA) transcript undergoes systematic processing, where multiple endonucleolytic and exonucleolytic cleavages remove the external and internal transcribed spacers (ETS and ITS). The processing sites and pathways for pre-rRNA processing have been deciphered in and, to some exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 155 publications
(299 reference statements)
2
30
0
Order By: Relevance
“…This preferential ITS1-first processing was first observed in xrn2 plants (Zakrzewska-Placzek et al, 2010), while the accumulation of 59ETS-first transcripts was reported in biogenesis of ribosomes in xenopus1 (brx1) plants (Weis et al, 2015b). These two pathways also coexist in rice plants, with the ITS1-first mode being the major pathway (Hang et al, 2018). Environmental stimuli or stress conditions might prevent the accumulation of pre-rRNA from the ITS1-first pathway (Weis et al, 2015a).…”
Section: Processing Of Pre-rrna: Two Alternative Pathwaysmentioning
confidence: 92%
“…This preferential ITS1-first processing was first observed in xrn2 plants (Zakrzewska-Placzek et al, 2010), while the accumulation of 59ETS-first transcripts was reported in biogenesis of ribosomes in xenopus1 (brx1) plants (Weis et al, 2015b). These two pathways also coexist in rice plants, with the ITS1-first mode being the major pathway (Hang et al, 2018). Environmental stimuli or stress conditions might prevent the accumulation of pre-rRNA from the ITS1-first pathway (Weis et al, 2015a).…”
Section: Processing Of Pre-rrna: Two Alternative Pathwaysmentioning
confidence: 92%
“…The processing of this pre-rRNA has been described in detail in both yeast and humans, but to date there is no clear outline in plants. However, possible models for A. thaliana (35) and Oryza sativa (43) have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…These two pre-rRNA processing activities require additional accessory proteins, such as RNA exosome components, Pumilio proteins, and many RNA-binding proteins. It has been reported that Arabidopsis and rice show similar pre-rRNA processing pathways, probably due to the similar anking sequences around the endocleavage sites of A2 and A3 in ITS1 [20], suggesting that RNA binding speci city is essential for the selection of cleavage sites. Recently, APUM23…”
Section: Typical Pumilio Proteins Have Tandem Repeats Of 8 Puf Domainmentioning
confidence: 99%